2017
DOI: 10.1111/cbdd.12980
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro evaluation, and 68Ga‐radiolabeling of CDP1 toward PET/CT imaging of bacterial infection

Abstract: Bacterial infections are a major concern in the human health sector due to poor diagnosis and development of multidrug-resistant strains. PET/CT provides a means for the non-invasive detection and localization of the infectious foci; however, the radiotracers available are either cumbersome to prepare or their exact contribution toward the imaging is not yet established. Human antimicrobial peptides are of interest for development as PET radiotracers as they are an integral component of the immune system, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…The hybrid imaging approach for imaging of deep infections it is postulated, when combined with a radioisotope, sites of infection can be identified using non-invasive nuclear imaging techniques and guide the subsequent surgical intervention and fluorescence guided surgery [74,75]. Research with other AMPs for pre-clinical imaging of infections is still ongoing [52,[76][77][78][79]. Recently, a synthetic analogue of the natural cyclic antimicrobial peptide depsidomycin ( 68 Ga-DOTA-TBIA101, Scheme 5), was investigated for its characteristic to target bacteria.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…The hybrid imaging approach for imaging of deep infections it is postulated, when combined with a radioisotope, sites of infection can be identified using non-invasive nuclear imaging techniques and guide the subsequent surgical intervention and fluorescence guided surgery [74,75]. Research with other AMPs for pre-clinical imaging of infections is still ongoing [52,[76][77][78][79]. Recently, a synthetic analogue of the natural cyclic antimicrobial peptide depsidomycin ( 68 Ga-DOTA-TBIA101, Scheme 5), was investigated for its characteristic to target bacteria.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…100 In 2017, Dutta et al radiolabeled and reported LL37, a human cathelicidin antimicrobial peptide ( 68 Ga-CDP1) that had higher uptake in in vitro bacterial cultures of S. aureus , E. coli and M. smegmatis , compared to eukaryotic cells. 101 Additional not bacteria-specific radiolabeled peptides such as the human neutrophil peptide ( 99m Tc-HNP-1), neutrophil elastase inhibitor peptide ( 99m Tc-HNE-2), human β-defensin ( 99m Tc-HBD-3), and vascular adhesion protein-1 selective peptide ( 68 Ga-DOTAVAP-P1), have been evaluated for bacterial imaging with variable results. 102105…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Although metabolic agents and radiolabeled sugars have shown potential in small animal trials and with a few bacterial species, they do not seem to have the same broad-spectrum bacterial affinity as TMP and have a significant background uptake of normal tissues [ 86 , 97 , 98 , 99 ].…”
Section: Specific Radiotracers Studied For Direct Visualization Of Ba...mentioning
confidence: 99%